Does Size Still Matter? Reassessing The Roles Of Firm Scale, Leverage And ESG In Driving Corporate Performance - Ima Kristina Yulita; Irene Rini Demi Pengestuti (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study investigates the moderating effects of leverage and firm size on the relationship between Environmental, Social, and Governance (ESG) performance and corporate financial performance. This study uses a quantitative approach with a causal design. Secondary data were obtained from Bloomberg Database during the 2016–2023 period. The research sample consisted of 47 non financial companies listed in Indonesia Stock Exchange or 376 company-year observations selected using a purposive sampling method. Financial performance variables were measured by return on equity (ROE), leverage by the debt-to-equity ratio (DER), company size by the natural logarithm of total assets, and ESG by the total ESG Disclosure score. Data analysis was performed using moderated regression analysis assisted (MRA) by SPSS software. The results show that ESG has a significant negative effect on ROE, indicating that implementing sustainability practices still has the potential to incur costs that depress short-term profitability. Conversely, DER has a significant positive effect on ROE, indicating that proportional use of debt can increase returns on equity. Moderation tests indicate that only DER moderates the relationship between ESG and ROE, while company size has no significant effect, either as a direct predictor or moderator. These findings emphasize that sustainability and funding structure must be viewed strategically and in balance. ESG commitments coupled with an efficient capital structure can create more optimal financial performance amidst the transition to a sustainable economy.